Übergang Schule-Beruf als Chancenverbesserungssystem – Zur Gestaltung von Lebensräumen und Entwicklung von Praktiken für den Übergang - Kremer, H.-Hugo; Otto, Franziska (bwp@ Berufs- und Wirtschaftspädagogik – online)
Sich wandelnde Bedingungen auf dem Ausbildungsmarkt, die daraus resultierenden veränderten Kompetenz- und Qualifikationsanforderungen sowie Anforderungen an eine lebensbegleitende berufliche Orientierung treffen insb. als (ausbildungs-)benachteiligt gekennzeichnete Jugendliche am Übergang Schule-Beruf. Jene Jugendliche münden in Maßnahmen des Übergangssystems wie die Ausbildungsvorbereitung (AV), wobei die konkreten Auswirkungen dieser Transformationsprozesse für diese Zielgruppe weitgehend unklar bleiben. In unserem Beitrag greifen wir die Überlegungen der Arbeitsgruppe 9+1 zum Übergangssystem verstanden als Chancenverbesserungssystem auf und diskutieren, was hierunter verstanden werden kann. Schließlich führen wir konkrete Anforderungen an das Chancenverbesserungssystem mit den Handlungsmöglichkeiten der Jugendlichen zusammen. Grundlegend verfolgen wir dabei nicht die Perspektive einer Anpassung der Jugendlichen an die Arbeitswelt, sondern fragen vielmehr danach, was Bildung leisten muss. Hierfür nehmen wir über qualitative Fallstudien die Perspektive der Jugendlichen sowie die Sichtweise des Bildungspersonals auf. In diesem Rahmen führen wir eine anforderungs- und subjektorientierte Perspektive zusammen und diskutieren u. a. anhand von Perspektiven auf das System, die curriculare Ebene, die Haltung der Bildungsakteur*innen, etc., was mit einer Gestaltung des Übergangssystems als Chancenverbesserungssystem konkret verbunden wäre.
Keywords: Übergangssystem; Selbstinszenierung; Chancenverbesserung; Subjektorientierung; Übergang Schule-Ausbildung

Rheologische Charakterisierung von Frischbeton : Entwicklung eines adaptiven Rheometers und Untersuchung wandgleitunterdrückender Messgeometrien - Josch, Sebastian

Numerical Computation of Capillary Bridges between Directly Resolved Rough Interfaces - Gräßer, Melanie

Measurement, Modelling, and Appli cation of Lubricant Properties at Extreme Pressures - Wingertszahn, Patrick; Schmitt, Sebastian; Thielen, Stefan; Oehler, Manuel; Magyar, Balázs; Koch, Oliver; Hasse, Hans; Stephan, Simon (Tribologie und Schmierungstechnik)
Lubricants play a central role in many technical applications, e.g. in bearings and gears as well as in machining processes. In such applications, lubricants are exposed to extreme conditions in the contact area. In lubrication gaps, the pressure can reach values up to 5 GPa. The thermophysical properties of lubricants, and in particular the viscosity, at such extreme conditions have an important influence on the friction and wear behavior of a tribosystem. Accordingly, reliable lubricant property models are a prerequisite for accurate tribological simulations, e.g. elastohydrodynamic lubrication (EHL) simulations. Presently, the vast majority of experimental thermophysical property data are only available up to 1 GPa. Thus, reliable and robust models with strong extrapolation capabilities to higher pressure are required. In this work, viscosity measurements of squalane in a temperature range be tween 20 °C and 100 °C and pressures up to 1 GPa were carried out. Based on that data, a physical model for the viscosity was developed. The model is built by combining a molecular-based equation of state with the so-called entropy scaling approach. Finally, we demonstrate how this fluid property model can be favorably integrated in an EHL simulation by an application programming interface (API). The novel hybrid modeling approach is promising for future applications.
Keywords: Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanical Engineering; Mechanics of Materials

When High‐Temperature Cesium Chemistry Meets Self‐Templating: Metal Acetates as Building Blocks of Unusual Highly Porous Carbons - Li, Jiaxin; Kossmann, Janina; Zeng, Ke; Zhang, Kun; Wang, Bingjie; Weinberger, Christian; Antonietti, Markus; Odziomek, Mateusz; López‐Salas, Nieves (Angewandte Chemie International Edition)
Self-templating is a facile strategy for synthesizing porous carbons by direct pyrolysis of organic metal salts. However, the method typically suffers from low yields (<4%) and limited specific surface areas (SSA<2000 m2 g−1) originating from low activity of metal cations (e.g., K+ or Na+) in promoting construction and activation of carbon frameworks. Here we use cesium acetate as the only precursor of oxo-carbons with large SSA of the order of 3000 m2 g−1, pore volume approaching 2 cm3 g−1, tunable oxygen contents, and yields of up to 15 %. We unravel the role of Cs+ as an efficient promoter of framework formation, templating and etching agent, while acetates act as carbon/oxygen sources of carbonaceous frameworks. The oxo-carbons show record-high CO2 uptake of 8.71 mmol g−1 and an ultimate specific capacitance of 313 F g−1 in the supercapacitor. This study helps to understand and rationally tailor the materials design by a still rare organic solid-state chemistry.
Keywords: CO2 Adsorption; Cesium Acetate; Cesium Effect; Porous Carbons; Supercapacitor

The Digital Twin of Humans

A new dual matrix burner for one-dimensional investigation of aerosol flames - Apazeller, Sascha; Gonchikzhapov, Munko; Nanjaiah, Monika; Kasper, Tina; Wlokas, Irenäus; Wiggers, Hartmut; Schulz, Christof (Proceedings of the Combustion Institute)
In spray-flame synthesis of nanoparticles, a precise understanding of the reaction processes is necessary to find optimal process parameters for the formation of the desired products. Coupling the chemistries of flame, solvent, and gas-phase species initially formed from the particle precursor in combination with the complex flow geometry of the spray flame means a special challenge for the modeling of the reaction processes. A new burner has been developed that is capable to observe the reaction of precursor solutions frequently used in spray-flame synthesis. The burner provides an almost flat, laminar, and steady flame with homogeneous addition of a fine aerosol and thus enables detailed investigation and modeling of the coupled reactions inde-pendent of spray formation and turbulent mixing. With its two separate supply channel matrices, the burner also enables the use of reactants that would otherwise react with each other already before reaching the flame. These features enable the investigation of a wide range of flame-based synthesis methods for nanoparticles and, due to the flat-flame geometry, kinetics models for these processes can be developed and validated. This work describes the matrix burner development and its gas flow optimization by simulation. Droplet-size dis-tributions generated by ultrasonic nebulization and their interaction with the burner structure are investigated by phase-Doppler anemometry. As an example for nanoparticle-for ming flames from solutions, iron-oxide nanoparticle-generating flames using iron(III) nitrate nonahydrate dissolved in 1-butanol were investigated. This effort includes measurements of two-dimensional maps of the flame temperature by a thermocouple and height-dependent concentration profiles of the main species by time-of-flight mass spectrometry. Exper-imental data are compared with 1D simulations using a reduced reaction mechanism. The results show that the new burner is well suited for the development of reaction models for precursors supplied in the liquid phase usually applied in spray-flame synthesis configurations.& COPY; 2022 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Christine Schwanecke: A Narratology of Drama: Dramatic Storytelling in Theory, History, and Culture from the Renaissance to the Twenty-First Century - Tönnies, Merle

Error analysis of BDF 1-6 time-stepping methods for the transient Stokes problem: velocity and pressure estimates - Contri, Alessandro; Kovács, Balázs; Massing, André (arXiv)
We present a new stability and error analysis of fully discrete approximation schemes for the transient Stokes equation. For the spatial discretization, we consider a wide class of Galerkin finite element methods which includes both inf-sup stable spaces and symmetric pressure stabilized formulations. We extend the results from Burman and Fernández [\textit{SIAM J. Numer. Anal.}, 47 (2009), pp. 409-439] and provide a unified theoretical analysis of backward difference formulae (BDF methods) of order 1 to 6. The main novelty of our approach lies in the use of Dahlquist's G-stability concept together with multiplier techniques introduced by Nevannlina-Odeh and recently by Akrivis et al. [\textit{SIAM J. Numer. Anal.}, 59 (2021), pp. 2449-2472] to derive optimal stability and error estimates for both the velocity and the pressure. When combined with a method dependent Ritz projection for the initial data, unconditional stability can be shown while for arbitrary interpolation, pressure stability is subordinate to the fulfillment of a mild inverse CFL-type condition between space and time discretizations.

Polymeric Networks Containing Amine Derivatives as Organocatalysts for Knoevenagel Reaction within Continuously Driven Microfluidic Reactors - Killi, Naresh; Bartenbach, Julian; Kuckling, Dirk (Gels)
The Knoevenagel reaction is a classic reaction in organic chemistry for the formation of C-C bonds. In this study, various catalytic monomers for Knoevenagel reactions were synthesized and polymerized via photolithography to form polymeric gel dots with a composition of 90% catalyst, 9% gelling agent and 1% crosslinker. Furthermore, these gel dots were inserted into a microfluidic reactor (MFR) and the conversion of the reaction using gel dots as catalysts in the MFR for 8 h at room temperature was studied. The gel dots containing primary amines showed a better conversion of about 83–90% with aliphatic aldehyde and 86–100% with aromatic aldehyde, compared to the tertiary amines (52–59% with aliphatic aldehyde and 77–93% with aromatic aldehydes) which resembles the reactivity of the amines. Moreover, the addition of polar solvent (water) in the reaction mixture and the swelling properties of the gel dots by altering the polymer backbone showed a significant enhancement in the conversion of the reaction, due to the increased accessibility of the catalytic sites in the polymeric network. These results suggested the primary-amine-based catalysts facilitate better conversion compared to tertiary amines and the reaction solvent had a significant influence on organocatalysis to improve the efficiency of MFR.
Keywords: Knoevenagel reaction; organocatalysis; polymeric gel dots; microfluidic reactions; polymeric networks

Classical solutions to Cauchy problems for parabolic–elliptic systems of Keller-Segel type - Winkler, Michael (Open Mathematics)
Abstract The Cauchy problem in R n {{\mathbb{R}}}^{n} , n ≥ 2 n\ge 2 , for u t = Δ u − ∇ ⋅ ( u S ⋅ ∇ v ) , 0 = Δ v + u , ( ⋆ ) \begin{array}{r}\left\{\phantom{\rule[-1.25em]{}{0ex}}\begin{array}{l}{u}_{t}=\Delta u-\nabla \cdot \left(uS\cdot \nabla v),\\ 0=\Delta v+u,\end{array}\right.\hspace{2.0em}\hspace{2.0em}\hspace{2.0em}\left(\star )\end{array} is considered for general matrices S ∈ R n × n S\in {{\mathbb{R}}}^{n\times n} . A theory of local-in-time classical existence and extensibility is developed in a framework that differs from those considered in large parts of the literature by involving bounded classical solutions. Specifically, it is shown that for all non-negative initial data belonging to BUC ( R n ) ∩ L p ( R n ) {\rm{BUC}}\left({{\mathbb{R}}}^{n})\cap {L}^{p}\left({{\mathbb{R}}}^{n}) with some p ∈ [ 1 , n ) p\in \left[1,n) , there exist T max ∈ ( 0 , ∞ ] {T}_{\max }\in \left(0,\infty ] and a uniquely determined u ∈ C 0 ( [ 0 , T max ) ; BUC ( R n ) ) ∩ C 0 ( [ 0 , T max ) ; L p ( R n ) ) ∩ C ∞ ( R n × ( 0 , T max ) ) u\in {C}^{0}\left(\left[0,{T}_{\max });\hspace{0.33em}{\rm{BUC}}\left({{\mathbb{R}}}^{n}))\cap {C}^{0}\left(\left[0,{T}_{\max });\hspace{0.33em}{L}^{p}\left({{\mathbb{R}}}^{n}))\cap {C}^{\infty }\left({{\mathbb{R}}}^{n}\times \left(0,{T}_{\max })) such that with v ≔ Γ ⋆ u v:= \Gamma \star u , and with Γ \Gamma denoting the Newtonian kernel on R n {{\mathbb{R}}}^{n} , the pair ( u , v ) \left(u,v) forms a classical solution of ( ⋆ \star ) in R n × ( 0 , T max ) {{\mathbb{R}}}^{n}\times \left(0,{T}_{\max }) , which has the property that if T max < ∞ , then both limsup t ↗ T max ‖ u ( ⋅ , t ) ‖ L ∞ ( R n ) = ∞ and limsup t ↗ T max ‖ ∇ v ( ⋅ , t ) ‖ L ∞ ( R n ) = ∞ . \hspace{0.1em}\text{if}\hspace{0.1em}\hspace{0.33em}{T}_{\max }\lt \infty ,\hspace{1.0em}\hspace{0.1em}\text{then both}\hspace{0.1em}\hspace{0.33em}\mathop{\mathrm{limsup}}\limits_{t\nearrow {T}_{\max }}\Vert u\left(\cdot ,t){\Vert }_{{L}^{\infty }\left({{\mathbb{R}}}^{n})}=\infty \hspace{1.0em}\hspace{0.1em}\text{and}\hspace{0.1em}\hspace{1.0em}\mathop{\mathrm{limsup}}\limits_{t\nearrow {T}_{\max }}\Vert \nabla v\left(\cdot ,t){\Vert }_{{L}^{\infty }\left({{\mathbb{R}}}^{n})}=\infty . An exemplary application of this provides a result on global classical solvability in cases when ∣ S + 1 ∣ | S+{\bf{1}}| is sufficiently small, where 1 = diag ( 1 , … , 1 ) {\bf{1}}={\rm{diag}}\hspace{0.33em}\left(1,\ldots ,1) .
Keywords: General Mathematics

Stabilization despite pervasive strong cross-degeneracies in a nonlinear diffusion model for migration–consumption interaction - Winkler, Michael (Nonlinearity)
Abstract A no-flux initial-boundary value problem for <?CDATA \begin{align*} \begin{cases} u_t = \Delta \big(u\phi(v)\big), \\[1mm] v_t = \Delta v-uv, \end{cases} \qquad \qquad (\star) \end{align*}?> <mml:mtable columnalign="right left right left right left right left right left right left" columnspacing="0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em" rowspacing="3pt">ut=Δ(uϕ(v)),vt=Δv−uv,(⋆) is considered in smoothly bounded subdomains of <?CDATA $\mathbb{R}^n$?> Rn with <?CDATA $n\geqslant 1$?> n⩾1 and suitably regular initial data, where φ is assumed to reflect algebraic type cross-degeneracies by sharing essential features with <?CDATA $0\leqslant \xi\mapsto \xi^\alpha$?> 0⩽ξ↦ξα for some <?CDATA $\alpha\geqslant 1$?> α⩾1 . Based on the discovery of a gradient structure acting at regularity levels mild enough to be consistent with degeneracy-driven limitations of smoothness information, in this general setting it is shown that with some measurable limit profile <?CDATA $u_\infty$?> u∞ and some null set <?CDATA $N_\star\subset (0,\infty)$?> N⋆⊂(0,∞) , a corresponding global generalized solution, known to exist according to recent literature, satisfies <?CDATA \begin{align*} \rho(u(\cdot,t))\stackrel{\star}{\rightharpoonup} \rho(u_\infty) \quad \textrm{in } L^\infty(\Omega) \quad\;\; \textrm{ and } \quad\;\; v(\cdot,t)\to 0 \quad \textrm{in } L^p(\Omega)\; \textrm{for all } p\geqslant 1 \end{align*}?> <mml:mtable columnalign="right left right left right left right left right left right left" columnspacing="0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em" rowspacing="3pt">ρ(u(⋅,t))⇀⋆ρ(u∞)in L∞(Ω) and v(⋅,t)→0in Lp(Ω)for all p⩾1 as <?CDATA $(0,\infty)\setminus N_\star \ni t\to \infty$?> (0,∞)∖N⋆∋t→∞ , where <?CDATA $\rho(\xi): = \frac{\xi^2}{(\xi+1)^2}$?> ρ(ξ):=ξ2(ξ+1)2 , <?CDATA $\xi\geqslant 0$?> ξ⩾0 . In the particular case when either <?CDATA $n\leqslant 2$?> n⩽2 and <?CDATA $\alpha\geqslant 1$?> α⩾1 is arbitrary, or <?CDATA $n\geqslant 1$?> n⩾1 and <?CDATA $\alpha\in [1,2]$?> α∈[1,2] , additional quantitative information on the deviation of trajectories from the initial data is derived. This is found to imply a lower estimate for the spatial oscillation of the respective first components throughout evolution, and moreover this is seen to entail that each of the uncountably many steady states <?CDATA $(u_\star,0)$?> (u⋆,0) of ( <?CDATA $\star$?> ⋆ ) is stable with respect to a suitably chosen norm topology.
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

A Riemann-Roch formula for singular reductions by circle actions - Delarue, Benjamin; Ioos, Louis; Ramacher, Pablo (arXiv:2302.09894)
We compute a Riemann-Roch formula for the invariant Riemann-Roch number of a quantizable Hamiltonian $S^1$-manifold $(M,ω,\mathcal{J})$ in terms of the geometry of its symplectic quotient, allowing $0$ to be a singular value of the moment map $\mathcal{J}:M→\mathbb{R}$. The formula involves a new explicit local invariant of the singularities. Our approach relies on a complete singular stationary phase expansion of the associated Witten integral.

Investigations of Ni-based methanation catalysts under dynamic conditions via hard X-ray spectroscopy - Strübbe, Sven
Im Rahmen dieser Dissertation wurden Katalysatoren, welche auf der thermischen Zersetzung von metallorganischen Gerüstverbindungen basieren, mittels Röntgenabsorptionsspektroskopie (XAS) und Röntgenemissionsspektroskopie (XES) untersucht. Durch diesen synthetischen Ansatz können hochdisperse Ni-basierte Katalysatoren eingebettet in einer Kohlenstoffmatrix gewonnen werden, welche für die Methanisierung von CO2 Einsatz finden. Diese sollen eine hohe Stabilität gegenüber Wasserstoffausfällen aufweisen, welche bedingt durch Wetterfluktuationen in der Gewinnung von grünem Wasserstoff auftreten. Um ein derartiges System gezielt gestalten zu können, ist ein detailliertes Verständnis zugrundeliegender chemischer Mechanismen und damit einhergehend elektronischer Strukturen der Katalysatorsysteme notwendig. Durch die detaillierte Analyse der Katalysator-Vorstufen mittels XAS konnte gezeigt werden, dass auch unter reduktiven Bedingungen in der thermischen Zersetzung Spuren von Ni(II) vorliegen und keine reine Nifcc-Struktur erreicht werden konnte. Eine detaillierte Auswertung der gleichen Präkatalysatoren mittels XES konnte durch eine neuartige Kombination von HERFD-XANES, theoretischer Berechnungen und VtC-XES einen eindeutigen Beweis für das Vorhandensein der gewünschten Kohlenstoffmatrix sowie Spuren von NiO im Präkatalysator liefern, welche sich vorteilhaft auf die spätere Aktivität im finalen Katalysator auswirken. Abschließend konnte mittels einer in-situ Untersuchung der Temperaturbereich, in dem sich die aktive Katalysatorspezies ausbildet, auf 80 bis 200 C eingegrenzt werden. Schließlich konnte ein eindeutiger Zusammenhang zwischen dem Verlust einer stabilisierenden Kohlenstoffschicht und einem Rückgang der Aktivität belegt werden.

Asymptotic Behavior of the Heat Semigroup on Certain Riemannian Manifolds - Grigor'yan, Alexander; Papageorgiou, Efthymia; Zhang, Hong-Wei (From Classical Analysis to Analysis on Fractals. A Tribute to Robert Strichartz, Volume 1)

Large-Time Behavior of Two Families of Operators Related to the Fractional Laplacian on Certain Riemannian Manifolds - Papageorgiou, Efthymia (Potential Analysis)
Abstract This note is concerned with two families of operators related to the fractional Laplacian, the first arising from the Caffarelli-Silvestre extension problem and the second from the fractional heat equation. They both include the Poisson semigroup. We show that on a complete, connected, and non-compact Riemannian manifold of non-negative Ricci curvature, in both cases, the solution with $$L^1$$ L 1 initial data behaves asymptotically as the mass times the fundamental solution. Similar long-time convergence results remain valid on more general manifolds satisfying the Li-Yau two-sided estimate of the heat kernel. The situation changes drastically on hyperbolic space, and more generally on rank one non-compact symmetric spaces: we show that for the Poisson semigroup, the convergence to the Poisson kernel fails -but remains true under the additional assumption of radial initial data.
Keywords: Analysis

Asymptotics for the infinite Brownian loop on noncompact symmetric spaces - Papageorgiou, Efthymia (Journal of Elliptic and Parabolic Equations)
Abstract The infinite Brownian loop on a Riemannian manifold is the limit in distribution of the Brownian bridge of length T around a fixed origin when $$T → +∞ $$ T → + ∞ . The aim of this note is to study its long-time asymptotics on Riemannian symmetric spaces G / K of noncompact type and of general rank. This amounts to the behavior of solutions to the heat equation subject to the Doob transform induced by the ground spherical function. Unlike the standard Brownian motion, we observe in this case phenomena which are similar to the Euclidean setting, namely $$L^1$$ L 1 asymptotic convergence without requiring bi- K -invariance for initial data, and strong $$L^{∞ }$$ L ∞ convergence.
Keywords: Applied Mathematics; Numerical Analysis; Analysis

Toward student agency in the selection and use of digital resources for learning and studying mathematics - Pepin, Birgit; Kock, Zeger-jan; Rezat, Sebastian (Handbook of Digital Resources in Mathematics Education)

Meta-Resources: Supporting the design of mathematics teaching and learning - Gueudet, Ghislaine; Pepin, Birgit; Rezat, Sebastian (Handbook of Digital Resources in Mathematics Education)

The role of digital technologies in transforming student learning landscapes - Rezat, Sebastian; Geiger, Vince (Handbook of Digital Resources in Mathematics Education)